Circ0038632 modulates MiR-186/DNMT3A axis to promote proliferation and metastasis in osteosarcoma - Tan, Xinyu; Zeng, Canjun; Li, Haomiao; Tan, Yeru; Zhu, Hongbo (Frontiers in Oncology, 2022)
Osteosarcoma is a highly malignant solid tumor with poor prognosis, early metastasis and rapid progression, and a high mortality rate that better therapeutic strategies are needed. Circ0038632, also known as circPLK1, is a tumor promotor in multiple cancers. However, its biological functions and molecular regulatory mechanisms in osteosarcoma remained unclear. To ascertain the function of circ0038632 in osteosarcoma, we checked its expression in cells as well as in tissues, and tested its abilities of proliferation and migration. Expression experiment manifested that circ0038632 showed an enhanced expression in osteosarcoma. Functional studies revealed that circ0038632 inhibition reduced cell proliferation and metastasis abilities of osteosarcoma. Mechanism studies revealed that circ0038632 sponged miR-186 to up-regulate the expression of DNA methyltransferase 3A (DNMT3A) to promote osteosarcoma progression. The circ0038632/miR-186/DNMT3A axis was involved in osteosarcoma progression. The results elucidated the potential application of circ0038632 as a novel diagnostic biomarker for progressive process of osteosarcoma.